Case Report: Severe Expressive Language Disorder of a Child with Laber\'s Congenital Amaurosis - Fariba Yadegari; Seyyed Jalal Sadrosadat (University of Social Welfare and Rehabilitation Sciences, 2001)
A 4 years old blind boy with leber's congenital amaurosis was referred for his severe expressive language problems. There was a considerable discrepancy between receptive and expressive language capabilities in favor of receptive ones. Behavioral problems such as temper tantrums, object dependency and cliche form movements, caused a referral to psychiatrist, which led to a short term drug prescription. Since it was revealed that he was able to perceive and reproduce rhythms presented to him, this capability was used for his speech training. This method of training have been appeared to be successful. His behavioral problems are controlled, he began to communicate vernally and his intellectual functioning is much better than prior to the therapy.